Pengaruh Pupuk Kompos Hasil Pengolahan Sampah Organik Rumah Tangga terhadap Pertumbuhan Bibit Matoa - Nawari; Thamrin; Siregar, Yusni Ikhwan; Efriyeldi (Jurusan Kehutanan Fakultas Pertanian Universitas Riau, 2025)
Processing household organic waste of plant parts into organic fertilizer can reduce pollution and greenhouse gas emissions in urban areas. The organic fertilizer produced supported sustainable agriculture. This study aims to determine the effect of applying organic compost fertilizer on the growth of Pometia pinnata seedlings propagated from seed germination in the nursery. The research design employed an experimental approach, specifically a completely randomized design. ANOVA and Tukey HSD were used to determine the effect of compost fertilizer doses on the growth of Pometia pinnata seedlings. The analysis shows that the morphological parameters of seedlings with compost fertilizer application were better than those of the control. The best dose that consistently provided better morphology parameters of seedlings was 75 g/polybag in a 10x20 cm size. Applying organic fertilizer supports the physiology of seedlings and provides proportional seed growth. Thus, the seedlings' sturdiness quotients are more potent than those of the control groups. Organic fertilizer production from household organic plant waste and planting Pometia pinnata for greening have the potential to mitigate climate change and enhance food security at the research location.